Lymphovascular space invasion and lack of downstaging after neoadjuvant chemotherapy are strong predictors of adverse outcome in young women with locally advanced breast cancer. (21st December 2015) - Khwaja, Shariq S.; Ivanovich, Jennifer; DeWees, Todd A.; Ochoa, Laura; Mullen, Daniel F.; Thomas, Maria; Margenthaler, Julie A.; Cyr, Amy; Naughton, Michael; Sanati, Souzan; Eberlein, Timothy J.; Gillanders, William E.; et al.
Abstract: Younger age diagnosis of breast cancer is a predictor of adverse outcome. Here, we evaluate prognostic factors in young women with locally advanced breast cancer (LABC). We present a retrospective review of 104 patients younger than 40 years with LABC treated with surgery, radiotherapy (RT), and chemotherapy from 2003 to 2014. Patient‐, tumor‐, and treatment‐related factors important for overall survival (OS), local/regional recurrence (LRR), distant metastasis (DM), and recurrence‐free survival (RFS) were evaluated. Mean age at diagnosis was 34 years (23–39 years) with a median follow‐up of 47 months (8–138 months). Breast‐conserving surgery was performed in 27%. Axillary lymph node dissection was performed in 85%. Sixty percent of patients received neoadjuvant chemotherapy with 19% achieving pathologic complete response (pCR), and 61% downstaged. Lymph node positivity was present in 91% and lymphovascular space invasion (LVSI) in 35%. Thirty‐two percent of patients had triple negative tumors (TN, ER‐/PR‐/HER2 nonamplified). Four‐year OS and RFS was 84% and 71%, respectively. Factors associated with worse OS on multivariate analysis include TN status, LVSI, and number of positive lymph nodes. LVSI was also associated with DM and LRR, as well as worse RFS. Downstaging was associated with improved 4 year RFS in patients receiving neoadjuvant chemotherapy (74% vs. 38%, P = 0.002). With high risks of recurrence and inferior OS compared to older women, breast cancer in young women can be difficult to treat. Among additional factors, presence of LVSI and lack of downstaging portends a particularly worse prognosis. Abstract : With high risks of recurrence and inferior overall survival compared to older women, breast cancer in young women can be difficult to treat. Among additional factors, presence of locally advanced breast cancer portends a particularly worse prognosis for all outcomes measured.